Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fmicb.2020.02119
|View full text |Cite
|
Sign up to set email alerts
|

Understanding LrgAB Regulation of Streptococcus mutans Metabolism

Abstract: Lack of LrgAB renders cariogenic Streptococcus mutans more sensitive to oxidative stress, as well as limits the capacity of this organism to re-uptake pyruvate upon starvation. This study was aimed at investigating the ecological and metabolic contribution of LrgAB to competitive fitness, using S. mutans strains, that either lack or overexpress lrgAB. These experiments revealed that impaired aerobic growth of the lrgAB mutant can be effectively restored by supplementation of pyruvate, and that perturbated expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…S. mutans possesses two holin/antiholin-like proteins, LrgAB, that are responsible for transporting pyruvate at the start of stationary phase. Research has suggested the existence of additional transporters or mechanisms for pyruvate to impact the growth of S. mutans (49). The genome of S. sanguinis lacks homologues of either gene, but S. sanguinis and other spxB-encoding species do release pyruvate in varying amounts to the surroundings, which can decrease the damaging effects of H 2 O 2 (21).…”
Section: Discussionmentioning
confidence: 99%
“…S. mutans possesses two holin/antiholin-like proteins, LrgAB, that are responsible for transporting pyruvate at the start of stationary phase. Research has suggested the existence of additional transporters or mechanisms for pyruvate to impact the growth of S. mutans (49). The genome of S. sanguinis lacks homologues of either gene, but S. sanguinis and other spxB-encoding species do release pyruvate in varying amounts to the surroundings, which can decrease the damaging effects of H 2 O 2 (21).…”
Section: Discussionmentioning
confidence: 99%
“…Although both smooth surface and sulcal caries in both BCC23 control groups were relatively low, they were greater than expected, based upon previous results with the mouse model that suggested autochthonous bacteria alone were poorly cariogenic when mice were fed the high sucrose diet (Ahn et al, 2020). It is unlikely that either BCC23 strain was directly responsible for the low levels of carious lesions as glycolysis and growth of S. sanguinis is repressed by prolonged acidification (Takahashi et al, 1997).…”
Section: Streptococcus Mutans Ua159 In Challenging Established S Sang...mentioning
confidence: 66%
“…It was shown previously in this same mouse model that when mice underwent mock inoculations (i.e. no exposure to exogenous bacteria), total smooth surface and total sulcal E score were each 0.55 and with dentinal severity scores of zero (Ahn et al, 2020). Notably, DNA samples recovered from oral swabs and molar sonicates of mice from both groups were examined by qPCR for S. mutans DNA, and results were negative in all cases.…”
Section: Influence Of Bcc23 Strains On Caries Incidence and Dentinal ...mentioning
confidence: 79%
“…Furthermore, S. mutans accounted for >50% of the total recovered bacteria from dental plaque of both WT and KO mice, indicating no significant differences in dental colonization by commensals as a whole. We have also recently shown that murine oral commensals did not produce any significant caries when mice were fed a highly cariogenic diet (Ahn et al, 2020). Although we cannot discount commensal streptococci accounting for a portion of the increased caries, it is unlikely that they would have accounted for a great majority of the observed difference.…”
Section: Amylase Expression In Humans and Cariesmentioning
confidence: 79%
“…At the same time, this dietary regimen represents a highly stringent test of the innate protective mechanisms associated with the oral cavity and, in particular, its hard tissues. Our rationale for using S. mutans UA159 is that it is widely used as a model in caries research, both in in vitro and animal studies, in which the genetic elements responsible for its colonization and virulence are being deciphered to better understand its pathogenesis and delineate potential therapeutic targets against mutans streptococci (Klein et al, 2010;Bowen et al, 2018;Ahn et al, 2020;Culp et al, 2021). The fact that the deletion of amylase expression resulted in a marked increase in caries answers our original question of whether its overriding effect is to either help promote or protect against caries.…”
Section: Amylase Caries and Dietmentioning
confidence: 99%